Predictive Outcome Modeling of Preoperative Clinical Symptoms and Electrodiagnostic Data in Tarsal Tunnel Surgery - Seidel, Geoffrey K.; Jamal, Salma Al; Weidert, Eric; Carington, Frederick; Andary, Michael T.; Millis, Scott R.; Loder, Brian G. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2021)
Background The relationship between tarsal tunnel syndrome (TTS), electrodiagnostic (Edx) findings, and surgical outcome is unknown. Analysis of TTS surgical release outcome patient satisfaction and comparison to Edx nerve conduction studies (NCSs) is important to improve outcome prediction when deciding who would benefit from TTS release.Methods Retrospective study of 90 patients over 7 years that had tarsal tunnel (TT) release surgery with outcome rating and preoperative tibial NCS. Overall, 64 patients met study inclusion criteria with enough NCS data to be classified into one of the following three groups: (1) probable TTS, (2) peripheral polyneuropathy, or (3) normal. Most patients had preoperative clinical provocative testing including diagnostic tibial nerve injection, tibial Phalen's sign, and/or Tinel's sign and complaints of plantar tibial neuropathic symptoms. Outcome measure was percentage of patient improvement report at surgical follow-up visit.Results Patient-reported improvement was 92% in the probable TTS group (n = 41) and 77% of the non-TTS group (n = 23). Multivariate modeling revealed that three out of eight variables predicted improvement from surgical release, NCS consistent with TTS (p = 0.04), neuropathic symptoms (p = 0.045), and absent Phalen's test (p = 0.001). The R2 was 0.21 which is a robust result for this outcome measurement process.Conclusion The best predictors of improvement in patients with TTS release were found in patients that had preoperative Edx evidence of tibial neuropathy in the TT and tibial nerve plantar symptoms. Determining what factors predict surgical outcome will require prospective evaluation and evaluation of patients with other nonsurgical modalities.
Keywords: tarsal tunnel syndrome; nerve conduction; medial plantar nerve; lateral plantar nerve; surgery; outcome modeling